Daukantas and Lietuvos senovės septyni paveikslai (‘Seven Pictures of Ancient Lithuania’) by Šatrijos Ragana - Bončkutė, Roma (Senoji Lietuvos literatūra, 2019)
The article considers the impact of Simonas Daukantas, the initiator of Lithuanian national historiography and a literary reformer, on the creative writings of Marija Pečkauskaitė (Šatrijos Ragana). It contains an analysis of the writer’s letters and short stories, but the main attention is focused on her historical narratives Lietuvos senovės septyni paveikslai (Seven Pictures of Ancient Lithuania). The analysis of the letters shows that in 1895, Šatrijos Ragana began studying the historical works by foreign authors and by Theodor Narbut; in 1896, inspired by the historical works by Henry Thomas Buckle, she resolved to write the history of Lithuania and from 1897, the concepts, expressions, and motives used by Daukantas started appearing in her writings.The analysis of ‘Seven Pictures of Ancient Lithuania’ (published in 1905) revealed that the number of Daukantas’s concepts and motives were borrowed from Jonas Mačiulis-Maironis’s Apsakymai apie Lietuvos praeigą (Short Stories about Lithuania‘s Past). It is possible that Šatrijos Ragana regarded Maironis’s shorter and simpler text more suited to the readers. However, she enriched her work with the descriptions of Lithuanian forests and motives of women’s heroism present in Daukantas’s Būdas senovės lietuvių, kalniečių ir žemaičių (The Character of the Ancient Lithuanians, Highlanders, and Samogitians) but absent from Maironis’s writings. In addition, she based the short stories ‘Živilė’ and ‘Apie Vilniaus įkūrimą’ (‘About the Founding of Vilnius’) on Daukantas’s History of Lithuania.Inspired by Daukantas, Šatrijos Ragana established her own approach to the history of Lithuania, which was well accepted by her readers. Moreover, Daukantas’s vocabulary, images, motives, and expressions affected not only Šatrijos Ragana’s historical narratives but all of her writings in general. It seems, therefore, that this intertextual study should be continued.
Keywords: Marija Pečkauskaitė; Šatrijos Ragana; Simonas Daukantas; Jonas Mačiulis-Maironis; history; literature; the Lithuanian language; sources